Effects of a Hemsball-Based Program on Children and Adolescents: A Systematic Review - Daniel González-Devesa; Nerea Blanco-Martínez; Carlos Ayán-Pérez (Journal of Functional Morphology and Kinesiology)
Objectives: This systematic review aims to critically analyze the available evidence on the effects of hemsball interventions in children and adolescents. Methods: This study followed PRISMA guidelines for identifying, selecting, and analyzing investigations. Systematic searches were conducted in five electronic databases (Web of Science, SportDiscus, Google Scholar, PubMed, and Scopus) until 23 February 2025. Only intervention studies with a control group assessing the effects of hemsball in children and adolescents were included. The methodological quality of randomized controlled trials was assessed using the PEDro scale, while comparative studies were analyzed using the MINORS index. Results: Out of 138 initially identified studies, five met the inclusion criteria. The included studies evaluated the effects of hemsball on balance, coordination, agility, manual dexterity, attention, and lower limb strength. The findings indicated significant improvements in balance, coordination, and manual dexterity in groups that participated in hemsball compared to controls. However, no significant differences were found in agility and lower limb strength. Conclusions: Hemsball programs appear to be effective in enhancing motor and coordination skills in children and adolescents, particularly in populations with special educational needs. However, the heterogeneity of the studies and the lack of information on intervention intensity limit the strength of the conclusions.